Surgical Approaches for Stage IVA Thymic Epithelial Tumors - Shapiro, Mark; Korst, Robert J. (Frontiers in Oncology, 2014)
Thymic epithelial tumors (TET) are rare mediastinal neoplasms that can metastasize to the pleural space (stage IVA). Complete surgical resection remains the backbone of therapy for patients with early stage TET, however, the role of surgery in the management of patients with stage IVA disease is not fully defined. Published reports in this regard are mainly small, retrospective and uncontrolled, with unclear inclusion criteria. Surgical options to manage pleural disease include metastatectomy, extrapleural pneumonectomy and metastasectomy/pleurectomy combined with heated intrapleural chemotherapy. The choice of the most appropriate surgical strategy needs to be individualized according to the quantity and location of disease, the patient’s overall condition, as well as operator and institutional expertise. In the majority of cases, metastatectomy of pleural implants will be sufficient to achieve a complete resection. The available literature suggests that in selected patients with stage IVA TET, delivery of neoadjuvant chemotherapy followed by complete resection is a viable treatment option that can be associated with long-term survival.